Persepsi Mahasiswa Akuntansi Terhadap Tujuan, Karakteristik, Dan Pengguna Informasi Akuntansi Syariah (Studi Empiris Pada Mahasiswa Akuntansi Universitas Syiah Kuala dan Universitas Malikussaleh) - Nanda Nadila Yutia; Nurlaila Nurlaila; Juliana Nasution (Universitas Labuhanbatu, 2022)
This study aims to determine the perception of accounting students who have and have not taken Islamic accounting courses on the objectives, characteristics, and level of interest of users of Islamic accounting information. The population in this study is all accounting students who are active at Syiah Kuala University and Malikussaleh University Class of 2018-2021. The method used in this study is Comparative with quantitative approach supported validation test, reliability test, and normality test data using SPSS 26 application. Testing the truth of the hypothesis proposed used Independent test sample t-Test and obtained the result that there are differences in perceptions of accounting students who have not and who have been mengampu Islamic accounting courses on the purpose, characteristics, and level of interest of users of Islamic accounting information. This is evidenced by the obtained pValue value<0.05. There are differences in perception between students who have and who have not taught Islamic accounting courses on the objectives, characteristics, and users of Islamic accounting information, as evidenced by the acquisition value.for X1 of 0.000, X2 of 0.002, and X3 of 0.003. The pValue value of the three variables is less than 0.05.